Making space: instructions in joint building activities - Wilton, Antje (Frontiers in Communication, 2025)
This contribution reports on an interdisciplinary study using multimodal space-based interaction analysis to investigate co-orientation, co-ordination and co-operation during interactional activities that structure the material space. The settings analyzed feature creative activities in ancient technology (making a sandal and building a hut) involving experts and novices. Participants in these interactions are giving, receiving and following instructions and requests in order to accomplish a joint project that has some relation to the (prehistoric) past, i.e., participants are engaged in creating heritage environments by making objects and architectural structures that reference the past through their design, materiality and production procedure. To accomplish their projects, participants activate, share and gather knowledge through joint cooperative and instructional activities, which makes these interactions particularly suitable for a form of multimodal interaction analysis that also takes the spatial and architectural affordances into account. By doing so, participants interact not only with each other, but also with their predecessors via the use and creation of material artefacts. The analysis shows that the establishment of boundaries as a fundamental human activity relies on multimodal instructions that employ means to create a joint mental image of the object or structure in its space-to-be in the interactional space to which participants orient until the structure is finished and becomes permanently available as a material object in the environment. The co-ordinated crafting and building activities are creative processes that become shared intercorporeal experiences in which knowledge and resources of the past are recovered, transformed and used to structure current and future actions.